PERTURBAÇÕES AUDITIVAS: O CONHECIMENTO COMO CAMINHO PARA A PREVENÇÃO (Revista Contexto & Educação, 2022)
Introduction: Serous otitis media and auditory processing disorder are difficult to diagnose disorders in young children, so prevention initiatives disseminate knowledge and awareness, allowing early identification of such disorders. With the collaboration of the University of Minho and the University of Algarve, a Conference Cycle was promoted inserted in a primary prevention action on a significant risk factor for language development: serous otitis media, a widespread pathology that affects young children mainly, and that can have an impact on language, as well as reaching an important pillar for linguistic development: central auditory processing. Objectives: sharing the experience of this cycle and the possible impact of the knowledge transmitted to the participants. Methodology: a questionnaire for sociodemographic characterization and perception/satisfaction was applied, and descriptive statistics was used for data analysis.  Results: the initial data showed a positive impact on the expansion of the participants' knowledge and their knowledge of the need for more training in this area. Conclusion: there is relevant interest in the theme of this Conference Cycle, being fundamental to continue to invest in these prevention activities due to its transformative potential in the professional practices of all those who deal directly with children.
Keywords: Serous Otitis Media; Prevention; Hearing; Speech therapy